2022
DOI: 10.1111/ele.13973
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in immune function and oxidative physiology across birds: The role of sexual selection

Abstract: Sex‐specific physiology is commonly reported in animals, often indicating lower immune indices and higher oxidative stress in males than in females. Sexual selection is argued to explain these differences, but empirical evidence is limited. Here, we explore sex differences in immunity, oxidative physiology and packed cell volume of wild, adult, breeding birds (97 species, 1997 individuals, 14 230 physiological measurements). We show that higher female immune indices are most common across birds (when bias is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Most species were captured at multiple locations and/or during multiple years and sampling occasions. We assessed the sex of each individual belonging to sexually dimorphic species based on morphological characters, while most individuals of (apparently) monomorphic species were sexed using molecular methods (for a detailed description of the molecular sexing method see Vincze et al, 2022 ). We collected blood samples (range 30–300 μl, depending on body size) by brachial venipuncture into heparinized capillaries as fast as possible after the bird was captured (always within 15 min; mean = 9.87 min, SD = 5.37).…”
Section: Methodsmentioning
confidence: 99%
“…Most species were captured at multiple locations and/or during multiple years and sampling occasions. We assessed the sex of each individual belonging to sexually dimorphic species based on morphological characters, while most individuals of (apparently) monomorphic species were sexed using molecular methods (for a detailed description of the molecular sexing method see Vincze et al, 2022 ). We collected blood samples (range 30–300 μl, depending on body size) by brachial venipuncture into heparinized capillaries as fast as possible after the bird was captured (always within 15 min; mean = 9.87 min, SD = 5.37).…”
Section: Methodsmentioning
confidence: 99%
“…Several functional terms relating to regulation of reactive oxygen species (ROS) were enriched. ROS levels influence a multitude of female reproductive processes including ovulation and maintenance of pregnancy (Rizzo et al, 2012), and sex differences in oxidative physiology have been demonstrated in wild birds (Vincze et al, 2022). Finally, many functional terms that were enriched for the turquoise module related to immunity, which suggests that sex-differences in immune processes may exist in the house sparrow, a phenomenon that has recently been demonstrated several species of wild birds (Valdebenito et al, 2021; Vincze et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…ROS levels influence a multitude of female reproductive processes including ovulation and maintenance of pregnancy (Rizzo et al, 2012), and sex differences in oxidative physiology have been demonstrated in wild birds (Vincze et al, 2022). Finally, many functional terms that were enriched for the turquoise module related to immunity, which suggests that sex-differences in immune processes may exist in the house sparrow, a phenomenon that has recently been demonstrated several species of wild birds (Valdebenito et al, 2021; Vincze et al, 2022). For the pink module that was negatively correlated with sex, many of the enriched functional terms related to ciliary motility and ciliary transport (the top term was the Reactome Pathway term “intraflagellar transport”, and the GO Biological Process terms “protein localization to cilium”, “Regulation of intraciliary retrograde transport”, “intraciliary retrograde transport”, and “Protein localization to non-motile cilium” were identified).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BKA against Escherichia coli (ATCC No 8739) was used to characterize the functional activity of a bird's constitutive innate immune system (Heinrich et al, 2016; Vincze et al, 2022). We used a duplicated assay described by French and Neumann‐Lee (2012), modified to low sample volumes by Eikenaar and Hegemann (2016).…”
Section: Methodsmentioning
confidence: 99%